1985
DOI: 10.1111/j.1751-1097.1985.tb03503.x
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals From the Photodecomposition of Bleomycin

Abstract: Abstract— Irradiation of bleomycin with light (λ > 320 nm) leads to a decrease in absorbance at 290 nm, which is suppressed by metal ions and by oxygen. Light‐induced oxygen consumption is diminished by the enzymes superoxide dismutase and catalase, implying that toxic reduced species of oxygen (O2 and H2O2) are formed during irradiation. Spin‐trapping measurements with 5,5‐dimethyl‐1‐pyrroline‐1‐oxide and 2‐methyl‐2‐nitrosopropane demonstrated that hydroxyl radical and methyl radical adducts also are generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In the epidermis, sporadic degenerative cells with dense and atrophied nuclei and eosinophilic and shrunken cytoplasms were seen in the basal layer. 4 hr. In the dermis, foci of slight edema were seen, which included separated fibroblasts with dense and irregularly shaped nuclei, eosinophilic granules, and occasionally necrotic cells (Fig.…”
Section: Auriclesmentioning
confidence: 95%
See 2 more Smart Citations
“…In the epidermis, sporadic degenerative cells with dense and atrophied nuclei and eosinophilic and shrunken cytoplasms were seen in the basal layer. 4 hr. In the dermis, foci of slight edema were seen, which included separated fibroblasts with dense and irregularly shaped nuclei, eosinophilic granules, and occasionally necrotic cells (Fig.…”
Section: Auriclesmentioning
confidence: 95%
“…Findings that differed from the 50-mg/kg group are described below. 4 hr. In the tip epidermis, cells with large nuclei were more multilayered.…”
Section: Auriclesmentioning
confidence: 95%
See 1 more Smart Citation
“…The finding that BHT protected against phototoxicity indicated that the generation of free radicals could play a part in causing phototoxicity. It is known that many compounds such as bleomyein (Antholine et al 1985) and porphyrin derivatives (Torinuki et al 1980) generate reactive oxygen in bringing about phototoxicity. Thus, one reason for the protective effect of BHT is probably related to the scavenging effect of free radicals directly generated in photochemical reactions; however, it is well known that reactive oxygen species are also generated in many steps of inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable mechanism for the formation of these pyrimidine radicals is the initial oxidation of the bases by electron transfer to the photoexcited drug molecules . Photogeneration of superoxide and hydroxyl radicals was observed when bleomycin and several of its metal complexes were exposed to near-UV and visible light in aerated aqueous solutions (Antholine et al, 1985). Carboquone, mitomycin C and streptomycin were also found to generate superoxide anions upon visible light exposure in aerated dimethylsufoxide solutions .…”
Section: Base Alterations Induced By Activated Oxygen Speciesmentioning
confidence: 99%